2018
DOI: 10.1007/s00737-018-0902-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived chronic stress on the fMRI correlates of attentional control in women managers

Abstract: The aims of the current study were to examine differences in brain responses to cognitive control in stressed and non-stressed women managers. Stress complaints are highly prevalent among active workers and play an important role in women managers mental health and cognitive functioning. Psychosocial stress has been associated with differential executive functions in this population, but little is known about the neural correlates underlying such differences. We examined brain responses of a particular group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…When analyzing the 11 studies 62 , 64 , 69 , 76 , 79 , 84 , 88 , 93 , 107 , 113 , 119 (425 participants) that administered inhibitory control tasks, greater activity was found in the claustrum, anterior cingulate cortex (ACC), and insula in the adversity exposure group compared with controls (9 studies 62 , 64 , 69 , 79 , 84 , 93 , 107 , 113 , 119 ; 52 coordinates; FWER-corrected P < .05; axis = −26, y-axis = 19; z-axis = 13) (eFigure 3 in Supplement 2 ). No group differences were identified when looking at studies that reported lower BOLD responses (6 studies 62 , 64 , 69 , 76 , 88 , 93 ; 14 coordinates).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzing the 11 studies 62 , 64 , 69 , 76 , 79 , 84 , 88 , 93 , 107 , 113 , 119 (425 participants) that administered inhibitory control tasks, greater activity was found in the claustrum, anterior cingulate cortex (ACC), and insula in the adversity exposure group compared with controls (9 studies 62 , 64 , 69 , 79 , 84 , 93 , 107 , 113 , 119 ; 52 coordinates; FWER-corrected P < .05; axis = −26, y-axis = 19; z-axis = 13) (eFigure 3 in Supplement 2 ). No group differences were identified when looking at studies that reported lower BOLD responses (6 studies 62 , 64 , 69 , 76 , 88 , 93 ; 14 coordinates).…”
Section: Resultsmentioning
confidence: 99%
“…We entered 282 coordinates from 34 studies 23 , 66 , 67 , 68 , 70 , 72 , 74 , 79 , 80 , 84 , 85 , 86 , 89 , 90 , 91 , 92 , 104 , 106 , 110 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 123 , 124 , 125 , 126 , 129 , 130 , 131 that reported greater BOLD responses in adversity exposure compared with controls in adulthood (2382 participants; mean [SD] age, 32.7 [6.4] years). The analysis yielded significantly greater right amygdala activations (FWER-corrected P < .001; x-axis = 24; y-axis = −4, z-axis = −17) (eFigure 9 in Supplement 2 ) and significantly lower activations in the middle frontal gyrus (Brodmann area 10; 1074 participants; mean [SD] age, 31.2 [7.1] years; 23 studies 65 , 68 , 70 , 76 , 77 , 80 , 87 , 88 , 91 , 94 , 99 , 101 , 104 , 106 , 111 , 114 , 116 , 123 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation